Tailoring services in opioid treatment programs for patients involved in America's criminal justice system: national associations and variation by state and Medicaid expansion status - George Pro; Brooke E. E. Montgomery; Nickolas Zaller (BMC, 2021)
Abstract Background Opioid treatment programs (OTPs) are the primary source of medication-assisted treatment (MAT) for many individuals with opioid use disorder, including poor and uninsured patients and those involved in the criminal justice (CJ) system. Substance use treatment services that are tailored to the unique needs of patients often produce better outcomes, but little national research has addressed characteristics associated with whether OTPs offer services specifically tailored to community members involved in the CJ system. Medicaid expansion under the Affordable Care Act has broadly strengthened MAT services, but the role of expansion in supporting MAT services that are specifically tailored towards CJ-involved populations remains unknown. Moreover, it is unknown whether the availability of tailored services varies between Medicaid expansion states. Methods We used the 2019 National Survey of Substance Abuse Treatment Services to identify OTPs in the US (n = 1679) and whether they offered services specifically tailored for CJ-involved patients. We used logistic regression to model the association between OTPs offering tailored services and state Medicaid expansion status, adjusted for state-level opioid overdose and community supervision rates. Results Nationally, only a quarter of OTPs offered services tailored to CJ populations, and the majority of OTPs (73%) were located in Medicaid expansion states. Compared to OTPs in non-expansion states, OTPs in expansion states demonstrated nearly double the odds of offering tailored services (adjusted odds ratio = 1.90, 95% confidence interval = 1.41-2.57, p < 0.0001). The predicted probability of offering tailored services varied by state; probability estimates for all expansion states were above the national mean, and estimates for all non-expansion states were below the national mean. Conclusion Our findings reiterate the role of Medicaid in promoting the adoption of comprehensive OTP services for CJ-involved populations. However, the proportion of OTPs that offered tailored services was relatively low, pointing to the need to continually strengthen Medicaid services and coverage.